2017
DOI: 10.1126/sciadv.1602025
|View full text |Cite
|
Sign up to set email alerts
|

The GH receptor exon 3 deletion is a marker of male-specific exceptional longevity associated with increased GH sensitivity and taller stature

Abstract: The d3-GHR genetic variant polymorphism modulates GH responsiveness throughout life span and positively affects male longevity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 53 publications
1
44
0
1
Order By: Relevance
“…S7 ). This replicated findings from a previous, locus-specific study that found an association with height in a different cohort ( 6 ) . That same study also suggested sex-specificity of the effect of GHRd3 on longevity, so the UK Biobank dataset was examined further to test if GHRd3 is correlated with any phenotypic effects in a sex-specific manner.…”
supporting
confidence: 89%
“…S7 ). This replicated findings from a previous, locus-specific study that found an association with height in a different cohort ( 6 ) . That same study also suggested sex-specificity of the effect of GHRd3 on longevity, so the UK Biobank dataset was examined further to test if GHRd3 is correlated with any phenotypic effects in a sex-specific manner.…”
supporting
confidence: 89%
“…A recent report of exceptional longevity in males associated with enrichment of an exon-3-deleted isoform of the GHR (d3-GHR) provides a new perspective of GHR isoforms and lifespan extension (228). An in-frame splicing of exon-2 to the exon-4 of GHR results in d3-GHR splice variant, with 22 amino acids less at the N-terminal than the full-length GHR.…”
Section: Lifespan In D3-ghr Variantsmentioning
confidence: 99%
“…Individuals with d3-GHR have low serum IGF-1and IGFBP1 levels yet surprisingly reduced levels of GH, GHR and GH binding protein (GHBP). The d3-GHR male offspring of centenarians were relatively tall and, remarkably, had a significantly increased lifespan (228) indicating augmented GH-GHR signaling (228). It is worth inquiring whether a reduced activity of metalloprotease TACE/ADAM17 action or regulators of it like TIMP3 (229,230) in cleaving the GHbound extracellular domain of the GHR homodimer generating GHBP is a causal link; or if there is a modified kinetics of interaction of the GH molecule with a 22-amino acid deleted extracellular domain of the d3-GH giving rise to a GHBP analog.…”
Section: Lifespan In D3-ghr Variantsmentioning
confidence: 99%
“…In addition, mice heterozygous for IGF1R knockout live 26% longer than the wild type mice [3]. Genetic polymorphism studies have identified genetic variations that are associated with extreme human longevity in centenarians, including FOXO3A [71], IGF1R [72], and GHR [73], suggesting that the IIS pathway may influence health and longevity in humans.…”
Section: Insulin/igf-1 Signalingmentioning
confidence: 99%